Stopping Smoking Reduces Mortality in Low‐Dose Computed Tomography Screening Participants. Issue 5 (May 2016) - Pastorino, Ugo; Boffi, Roberto; Marchianò, Alfonso; Sestini, Stefano; Munarini, Elena; Calareso, Giuseppina; Boeri, Mattia; Pelosi, Giuseppe; Sozzi, Gabriella; Silva, Mario; Sverzellati, Nicola; Galeone, Carlotta; et al.
ABSTRACT : Introduction: : The National Lung Screening Trial has achieved a 7% reduction in total mortality with low‐dose computed tomography (LDCT) screening as compared with in the chest radiography arm. Other randomized trials are under way, comparing LDCT screening with no intervention. None of these studies was designed to investigate the impact of smoking habits on screening outcome. In the present study, we tested the effect of stopping smoking on the overall mortality of participants undergoing repeated LDCT screening for many years. Methods: : Between 2000 and 2010, 3381 smokers aged 50 years or older were enrolled in two LDCT screening programs. On the basis of the last follow‐up information, subjects were divided into two groups: current smokers throughout the screening period and former smokers. Results: : With a median follow‐up time of 9.7 years and a total of 32, 857 person‐years (PYs) of follow‐up, a total of 151 deaths were observed in the group of 1797 current smokers (17, 846 PYs) versus 109 among 1584 former smokers (15, 011 PYs), corresponding to mortality rates of 8.46 and 7.26 for every 1000 PYs, respectively. Compared with current smokers, former smokers had an adjusted mortality hazard ratio of 0.61 (95% confidence interval: 0.44–0.83), with a 39% reduction in mortality. A similar reduction in mortality was observed in the subset of 712 late quitters, with a hazard ratio of 0.65 (95% confidence interval: 0.44–0.96). Conclusions: : Stopping smoking significantly reduces the overall mortality of smokers enrolled in LDCT screening programs. The beneficial effect of stopping smoking on total mortality appears to be threefold to fivefold greater than the one achieved by earlier detection in the National Lung Screening Trial.